Imaging technologies for the detection of sinus pathologies of odontogenic origin. A review - Lozano González, Óscar (2021)
Sinus pathologies of odontogenic origin (SPO) are common in the clinical consultation; however, the dentist has some complications to detect them because their discovery is usually incidental and through imaging studies that, in most cases, are of low quality. The objective of this review is to describe the pertinent imaging resources that allow the detection of the most frequent SPO and, at the same time, carry out an updated review of the scientific literature in order to recognize the imaging of both the maxillary sinus and the dental organs. The scientific literature focused on this topic, published between 2014 and 2020, was consulted. The review showed two important results: the first is that Cone Beam Tomography (CBCT) represents the imaging modality with the best performance for the detection of SPO by what can be considered the gold standard for this purpose. The second is that the most frequent SPO is sinus mucositis, which is related to odontogenic conditions such as periapical lesions and periodontal affectations. Although Cone Beam Computed Tomography (CBCT) is the most appropriate tool to detect SPO compared to images obtained by 2D devices, there are also other alternatives such as magnetic resonance imaging and ultrasonography, which seem to have a promising future.